KONSEP KEADILAN SOSIAL DALAM PEMIKIRAN AL-MAWARDI DAN RELEVANSINYA BAGI TATA KELOLA PEMERINTAHAN ISLAM (IBTIKAR: Jurnal Studi Islam dan Sosial, 2025)
This article discusses Al-Mawardi's thinking on social justice as a key principle in the Islamic system of governance, as well as its relevance in the context of contemporary governance. Al-Mawardi, through his monumental work Al-Ahkam al-Sultaniyyah, emphasized the importance of justice as the foundation of legitimate political power and an instrument for maintaining social stability. The concept of justice in Al-Mawardi's thought not only includes the equitable distribution of power and resources, but also touches on aspects of the morality of leaders, the protection of people's rights, and the mechanism of supervision against abuse of power. This article uses a qualitative approach with literature studies as the main method to explore Al-Mawardi's ideas, then examines their relevance in modern governance systems, including the principles of transparency, accountability, and public participation. The findings of the study show that even though it was born in a medieval context, Al-Mawardi's thought still has a strong normative and philosophical impetus in responding to the challenges of inequality and ethical crises in today's government. Therefore, Al-Mawardi's thinking can be a conceptual inspiration for the formulation of Islamic governance that is just, benefit-oriented, and responsive to social realities.